Thermal performance of double-layer porous copper strips mounted as hollow cylinders (Periodicals of Engineering and Natural Sciences, 2021)
The thermal performance of thin double-layer porous copper strips was experimentally examined. To fabricate double-layer porous copper strips the lost carbonate sintering procedure was employed. The suitability of these materials for applications of heat sink was systematically investigated. Then, the thermal properties of an external heat transfer facility, which operates under a forced heat convection process using air as a coolant, were assessed. In this case, a cylindrical heating system was chosen to be used with the air passing across the samples at mass rates of 0.1- 0.5 kg/s. The temperatures of the air at the inlet and outlet in addition to the surface temperature of the system were monitored and used to determine the heat transfer performance. The results showed that both the porosity and roughness in a surface of a material could play an essential role in such type of material in enhancing heat transfer at a surface of the system. With high porosity and surface roughness of up to 82% and Ra ≤ 1.21 mm, respectively, the sample achieved a thermal transmittance 57% higher than that of a reference smooth copper sheet under the same Reynolds number. Finally, the heat transmittance of the examined porous sheets in the current research increased with the bulk porosity and surface roughness.